Performance of spent bleaching earth as cement replacement in concrete - Chia, Khai Tee (2010)
Spent bleaching earth SBE)is an industrial waste,mainly generated from the edible oil processing.SBE is obtained by ultrasonic extraction where hexane act as solvent.By replacing cement with SBE,waste disposal problem of SBE can be reduced and economical concrete can be produced.This study is to investigate the engineering properties of concrete with 50% and 60% of spent bleaching earth (SBE) as replacement of cement.The field of studies also covers important parameters including compressive strength,flexural strength, and drying shrinkage in determining the engineering properties.Total of 54 cubes (150 x 150 x150 mm) and 54 prisms (100 x 100 x 500 mm) were prepared in three different percentage of cement.These entire samples were cured under air curing and water curing.Through the observation,the spent bleaching earth showed lower early strength gain.However,60% SBE concrete show lower result than 50% SBE,which mean that the percentage of SBE need to reduce to ensure the concrete achieved its specific strength.This study offered that the SBE as the new material implementation of lightweight composite design and construction utilizes existing technologies which lead to another choice in the current markets for greener environment.